2020
DOI: 10.1590/s1980-220x2018029003575
|View full text |Cite
|
Sign up to set email alerts
|

Violence in intimate relationships from the point of view of adolescents: perspectives of the Complexity Paradigm,

Abstract: Objective: To analyze adolescents’ perceptions about intimate violence from the perspective of the Complexity Paradigm. Method: A qualitative approach configured as strategic social study. The study participants were adolescents between 15 and 18 years old, attending high school in two public schools in a city in the interior of São Paulo State, Brazil. Data collection was performed through a focus group and a semi-structured interview as a complement. Data analysis was based on the dialogical, organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
(20 reference statements)
0
5
0
7
Order By: Relevance
“…Most adolescents who did not physically abuse their boyfriends/girlfriends had already ended the relationship, while the perpetrators remained in the relationship. Qualitative research carried out with adolescents of both genders, in the interior of São Paulo, revealed that the duration of the relationship was configured as a motivating element in dating violence, according to the participants' conception (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most adolescents who did not physically abuse their boyfriends/girlfriends had already ended the relationship, while the perpetrators remained in the relationship. Qualitative research carried out with adolescents of both genders, in the interior of São Paulo, revealed that the duration of the relationship was configured as a motivating element in dating violence, according to the participants' conception (20) .…”
Section: Discussionmentioning
confidence: 99%
“…In a way that most adolescents involved in the condition of victims of sexual assault or perpetrators of physical abuse considered that conflicts occurred few times in their relationships. Due to daily contact with situations of violence in society, adolescents may consider abusive behaviors in their relationships as acts of love, reaffirming the crystallization and invisibility of the dyad affect-aggression of the problem (20) .…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos adolescentes que não cometeram abusos físicos contra seus(suas) namorados(as) já havia terminado o relacionamento, enquanto que os perpetradores permaneciam no relacionamento. Pesquisa qualitativa realizada com adolescentes de ambos os sexos, no interior de São Paulo, revelou que o tempo de relacionamento se configurou um elemento motivador da violência no namoro, na concepção dos participantes (20) .…”
Section: Discussionunclassified
“…De maneira que a maioria dos adolescentes envolvidos na condição de vítimas de agressões sexuais ou de perpetradores de abusos físicos considerou que os conflitos ocorreram poucas vezes nos seus relacionamentos. Devido ao convívio no cotidiano com situações de violência na sociedade, os adolescentes podem considerar comportamentos abusivos em seus relacionamentos como atos de amor, reafirmando a cristalização e invisibilização da díade afeto-agressão da problemática (20) .…”
Section: Discussionunclassified
“…The expectations of the roles of being a man and being a woman in the Brazilian society, present at the social level but with direct consequences for the others, are reinforced by the adolescents. Traditional gender norms endorse beliefs that men must be in a dominant social position that gives them privileges and power over women ( 24 ) .…”
Section: Discussionmentioning
confidence: 99%